Experiências de estudantes indígenas do povo Haliti Paresi nas escolas públicas em Tangará da Serra-MT (2008-2023) - Castoldi, Edson César (2024)
This dissertation is a study about the experiences lived by students and former students from Haliti Paresi people in non-indigenous public schools located in the city of Tangará da SerraMT. It aims to raise hypothesizes and possibilities for understanding the process of leaving and returning of the young students from this community who annually leave their respective village to attend rural or urban non-indigenous schools in the city of Tangará da Serra-MT. The interviews highlight the difficulties they face, such as cultural differences, long distances from their community, the Portuguese language, prejudices, housing, food, transport and different teaching methods. To accomplish this, a time frame was drawn up between 2008 and 2023, which served as the basis for interviews, seven in all. These included four students and three former students, aiming to gather information about their dreams, desires, difficulties and desire to return to the core of the Haliti people in order to contribute to the development of their community with the knowledge they have acquired. To understand the current historical situation of the Haliti Paresi people it is necessary to reflect on anthropological, archaeological and historical studies concerning the European colonization process established since 1500 in the onward current territory known as Brazil. Additionally, the study considered the consequences suffered by the indigenous peoples, over more than 500 years of colonization, domination, enslavement and extermination during different historical periods: colonial, imperial and republican. It is worth highlighting the forms of resistance used by the indigenous people over time, such as alliances, treaties, wars and escapes, among others which have guaranteed their survival against the colonization process. Specifically, the Haliti Paresi people, despite being colonized, enslaved, exploited and exterminated for more than five centuries, the Haliti Paresi people currently keep their cultural traditions alive and contribute significantly to the development of the city of Tangará da Serra and surrounding cities.